Fasudil Attenuated 6-OHDA Cytotoxicity in PC12 Cells through Inhibition of JAK/STAT and Apoptosis Pathways - Samira Barangi; Seyyed Masoud Hosseini; Gholamreza Karimi; Soghra Mehri (Tabriz University of Medical Sciences, 2023)
Background: 6-Hydroxydopamine (6-OHDA) is widely used to induce neurotoxicity and investigate the mechanisms of Parkinson disease. 6-OHDA causes cell injury through various mechanisms including oxidative stress, inflammation and apoptosis. The selective Rho-kinase inhibitor, fasudil displays neuroprotective effects in several neurodegenerative disorders. The aim of this study was to assess the protective effect of fasudil in PC12 cytotoxicity induced by 6-OHDA. Methods: PC12 cells were exposed to 5, 10, 25, and 50 µM of fasudil concentrations. After 24 h, the IC50 value of 6-OHDA (150 µM) was added. Twenty-four hours later, the viability of cells was evaluated via MTT assay and the formation of reactive oxygen species (ROS) was measured by the fluorimetric method. At the 50 µM concentration of fasudil, with or without 6-OHDA, the changes of protein levels including STAT3, P-STAT3, JAK2, P-JAK2, and caspase-3 were determined via western blotting. Results: Our results showed that 6-OHDA increased the intracellular level of ROS, reduced cell viability, upregulated p-STAT3/STAT3 and p-JAK2/JAK2 ratios and significantly raised cleaved caspase-3 in comparison to control group. Furthermore, pretreatment of cells with fasudil (50 µM) for 24 h could reverse all changes induced by 6-OHDA. Conclusion: 6-OHDA caused cytotoxicity in PC12 cells through inducing oxidative stress and activating JAK/STAT and apoptosis pathways, while pretreatment with fasudil exhibited protective effect on 6-OHDA-induced neurotoxicity via the inhibition of oxidative stress and prevention of these pathways.